Synthesis of Phosphorylated Sugar Palm (Aren) Starch Using Low Level Sodium Tripolyphosphate (STPP) (Jurnal Bahan Alam Terbarukan, 2019)
Sugar palm or aren (Arenga pinnata) is a traditional source of starch widely cultivated throughout Indonesia. Despite its potentiality to be used as feedstock for food industries, there has been very little research reported on sugar palm starch characterization and modification. This paper describes a preliminary experimental study on the chemical modification, i.e. phosphorylation of sago palm starch using low level of Sodium tripolyphosphate (STPP), and characterization of some important physicochemical and functional properties of the modified products. Starch phosphate synthesis was conducted at an initial pH of 9, reaction temperatures of 120-140 oC, and STPP intakes of 0.5-1.5%-weight based on dry starch. The experimental result shows that Degree of Substitution (DS) of the obtained products is accessible in the range of 0.0013 – 0.0068. An increase in reaction temperature as well as STPP intake leads to products with higher DS values. The modified starch products exhibit higher swelling power (16.57-24.81 g/g) and solubility (9.12-22.79 %-w/w) compared to native sugar palm starch (swelling power and solubility of 14.50 g/g and 7.91 %-w/w, respectively). Phosphorylated starch products also have significantly improved paste clarity clarity and water/ oil absorption capacity compared to native sugar palm starch. The result suggests that phosphorylation is a promising method to enhance the properties of sugar palm starch.